PENTINGNYA POSISI SECONDARY MORTGAGE FACILITY (SMF) DAN EFEKTIVITAS SEKURITISASI KREDIT PEMILIKAN RUMAH ( KPR) PERBANKAN DI MASA DEPAN - Prasetyowati, Riris Aishah (MONETER, 2013)
Importance of outstanding Secondary Mortgage Facility (SMF) have strong relationship with effectiveness of Commercial Credit Home Ownership (KPR) Banking. Both of them can make great impact for the future of country. To achieve this objective, every person must understand the learning process in securitization SMF Credit Home ownership Many aspect of sekuritisasi KPR have been found in SMF that operations in Indonesia. All of them have similiar situation of SMF and have to deal with it to make a good progress for effectiveness of securitization KPR for country in prosperity with the future.